The wolves of K Street : the secret history of how big money took over big government - Mullins, Brody; Mullins, Luke (Simon & Schuster, 2024)
Two veteran investigative journalists trace the rise of the modern lobbying industry through the three dynasties--one Republican, two Democratic--that have enabled corporate interests to infiltrate American politics and undermine our democracy. --